RANCANG BANGUN ANIMASI PERCAKAPAN BAHASA INGGRIS BERBASIS 2D MENGGUNAKAN TEKNIK FRAME BY FRAME - Hasanuddin, Hasanuddin; Agus Jayadi; Putri Ayu Firmansani (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2022)
This research focuses on the Animation Design of “English Conversation”2D Based Using Frame By Frame Technique. The purpose of this research is to facilitate teacher in delivering English conversation material and to increase interest student learning and increase enthusiasm for learning. The method used is the method research and development (R&D) which can be defined as “a scientific way of researching, designing, producing and testing questionnaires and product validity that have been generated".The results showed that this animated video was successfully made (designed and built) to make it easier for language teachersbased on the percentage of validation results that is 92.30% with very decent criteria and can increase students' interest in learninglearning and enthusiasm in learn English conversation based on the percentage of learning questionnaire results without using animated videos, which is 43%with less criteria and the percentage of results from learning questionnaires using animated videos is 84% with decent criteria, so it can be declared increased 41%.